Juli og August Maaneder 1867. Agerdyrkningsberetning. (Fra Begyndelsen af September). - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Juli og August Maaneder 1867. Agerdyrkningsberetning. (Fra Begyndelsen af September).